Prostanoids in bronchoalveolar lavage fluid do not predict outcome in congenital diaphragmatic hernia patients - H. Ijsselstijn; F. J. Zijlstra; J. C. De Jongste; D. Tibboel (Mediators of Inflammation)
Vasoactive prostanoids may be involved in persistent pulmonary hypertension (PPH) in infants with a congenital diaphragmatic hernia (CDH). We hypothesized that increased levels of prostanoids in bronchoalveolar lavage (BAL) fluid would predict clinical outcome. We measured the concentrations of 6-keto-prostaglandin F1α (6-keto-PGF1α), thromboxane B2 (TxB2), protein, albumin, total cell count, and elastase-α1-proteinase-inhibitor complex in BAL fluid of 18 CDH patients and of 13 control subjects without PPH. We found different concentrations of prostanoids in BAL fluid of CDH patients with PPH: infants with a poor prognosis had either high levels of both 6-keto-PGF1α and TxB2 compared to controls, or high levels of 6-keto-PGF1α only. TxB2 levels showed a large variability in all CDH patients irrespective of outcome. We conclude that prostanoid levels in BAL fluid do not predict clinical outcome in CDH patients.